Influence of nitrogen, phosphorus and potassium on composition of leaf and its relationship with fruit yield in 'Allahabad Safeda' guava (Psidium guajava) on an Alfisol - KOTUR, S C; RAMKUMAR, RAMKUMAR; SINGH, H P (The Indian Journal of Agricultural Sciences, 2013)
In a field experiment on 8-year-old 'Allahabad Safeda' guava (Psidium guajava L.), an increase in N level (0-80g/tree/year) significantly increased the N and K but decreased the P and Cu contents of leaf. Calcium content of leaf increased up to 500 g N but decreased at higher levels of N. The increase in P level (0-349 g) significantly increased the N, P and K in leaf. Calcium and Mg in leaf increased up to 131 g P, whereas higher P application decreased it. Iron content continuously decreased with increase in P application up to 262 g P/tree. Maximum Mn content was observed at 175 kg P/plant. Similarly, increase in K application (0-482 g) increased the N, P and K contents of leaf. A quadratic relationship was observed between fruit yield and nutrient applied as well as its content in leaf. Accordingly, the maximum fruit yield was obtained at 583 g N/plant 271 g P/plant and 399 g K/plant and at 1.89% N, 0.16% P and 2.34% K in the leaf. The range of nutrients associated with maximum fruit yield was 1.8-2.0% N, 0.12-0.16% P, 1.46-2.08% K, 1.13-1.69 Ca, 0.25-0.31 % Mg, 266-345 g/g Fe, 176-267 mug/g Zn and 10-13 mu-g/g Cu in the leaf